Permissive Parenting Style and College Self-Efficacy as Determinants of College Adjustment [Pola Asuh Permisif dan College Self-Efficacy Menentukan College Adjustment Mahasiswa] - Stella Olivia Alda Rianto; Yuspendi Yuspendi; Jane Savitri (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2020)
Many tertiary students do not complete all the steps of their tertiary education because they encounter difficulties in adjusting themselves to university life. The aim of this research was to determine the role of upbringing (by both father and mother) and the “college self-efficacy” (the self-confidence of the students in completing their study obligations) regarding college adjustment (CA) [US term] of first-year students of the Faculty of Technology of University X [name concealed], in Bandung, West Java, Indonesia. 139 students were involved in this research, and completed an instrument to measure the research variables. The research data was processed, using regression analysis, to determine the contributions of patterns of upbringing and self-efficacy of the students, regarding college adjustment. Based upon the analysis conducted in the research, the results indicated that the parenting style and college self-efficacy generally had a role in the college adjustment of the student. However, the results more especially indicated that a pattern of permissive maternal upbringing had a significant negative contribution to their CA, and that college self-efficacy had a significant positive contribution to that CA. This paper then discusses the magnitude of the role of the parent, compared to the self-efficacy of the student in his or her achievements, when undertaking tertiary education. Banyak mahasiswa tidak menyelesaikan jenjang sarjana karena mengalami hambatan penyesuaian diri di masa kuliah. Tujuan dari penelitian ini adalah mengetahui peran pola pengasuhan (ayah dan ibu) dan college self-efficacy (keyakinan diri mahasiswa menyelesaikan kewajiban studi) terhadap college adjustment (CA) mahasiswa Fakultas Teknik tahun pertama Universitas X Bandung. 139 mahasiswa tergabung dalam penelitian ini dan mengisi instrumen yang mengukur variabel penelitian. Data penelitian diolah dengan analisis regresi untuk menentukan kontribusi pola asuh dan keyakinan diri mahasiswa terhadap college adjustment. Berdasarkan analisis yang dilakukan dalam penelitian ini, hasil penelitian menunjukkan parenting style dan college self-efficacy secara umum berperan terhadap college adjustment mahasiswa. Akan tetapi, hasil lebih khusus menunjukkan pola asuh permisif ibu berkontribusi signifikan negatif terhadap CA, dan college self-efficacy berkontribusi signifikan positif terhadap CA. Tulisan ini kemudian membahas besaran peran orangtua apabila dibandingkan dengan keyakinan diri mahasiswa dalam keberhasilannya menempuh pendidikan tinggi.